1996
DOI: 10.1177/000331979604700302
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lower Limb Arterial Assessments Using Color-Duplex Ultrasound and Ankle/Brachial Pressure Index Measurements

Abstract: The strength of agreement between two noninvasive methods of assessing lower limb arterial disease and their relationship to patient symptoms following exercise have been investigated. Color-duplex ultrasound (CDU) and ankle/brachial pressure index (ABPI) (before and afer exercise) measurements were obtained from 200 consecutive patients referred to a vascular investigations laboratory. From these patients, 290 limbs were available for study, comprising limbs without previous vascular surgery, from patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…The accuracy of the ABPI can be marginally improved by the inclusion of a standard treadmill exercise test and postexercise ABPI, and future studies should consider including this in their protocol. 31 Its accuracy can also be reduced in patients with calcified blood vessels, such as in those with diabetes or chronic renal failure, although this did not appear to be a problem in our study because less than half of the 7% subjects who had a raised ABPI of Ͼ1.3 in either leg had these diseases. We do, of course, recognize that calcification would be an issue for general PAD screening, and it would therefore be appropriate to evaluate this further in future studies.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The accuracy of the ABPI can be marginally improved by the inclusion of a standard treadmill exercise test and postexercise ABPI, and future studies should consider including this in their protocol. 31 Its accuracy can also be reduced in patients with calcified blood vessels, such as in those with diabetes or chronic renal failure, although this did not appear to be a problem in our study because less than half of the 7% subjects who had a raised ABPI of Ͼ1.3 in either leg had these diseases. We do, of course, recognize that calcification would be an issue for general PAD screening, and it would therefore be appropriate to evaluate this further in future studies.…”
Section: Discussionmentioning
confidence: 53%
“…Future research could also assess modified ABPI calculations that have recently been reported to improve the sensitivity of PAD detection. 32 Other diagnostic references that could have been used to evaluate the PPG technology include color-coded duplex ultrasound imaging with 83% agreement with resting ABPI 31 and also contrast-enhanced magnetic resonance angiography. 33 Although these imaging-based assessments are costly and resource intensive, they would have the advantage over ABPI in that they can provide some additional information about disease location.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical basis of ABPI is supported by obtaining ABPI ratios against findings in peripheral angiography,19–24 as well as from Doppler ultrasound as gold standard 25…”
Section: Theoretical Basis Of the Abpi Testmentioning
confidence: 99%
“…ABPI was biased in the detection of more severe disease and its utility in patients with low-grade stenosis and with high-risk of heavy arterial calcification was unreliable. [1314] All these techniques were limited primarily because of the non-linear relationship between CV risk factors and the actual development of disease, their high cost, invasiveness, limited availability, advanced setup requirements, exposure to radiation and contrast, and decreased sensitivity and specificity. These factors posed a greater challenge in diagnosing atherosclerosis in low-risk individuals who may otherwise not require aggressive treatment.…”
Section: Conventional Diagnostic Modalities and Their Limitationsmentioning
confidence: 99%